Magnesium and Hearing - Cevette, Michael J.; Vormann, Jürgen; Franz, Kay (Journal of the American Academy of Audiology, 2003)
The last several decades have revealed clinical and experimental data regarding the importance of magnesium (Mg) in hearing. Increased susceptibility to noise damage, ototoxicity, and auditory hyperexcitibility are linked to states of Mg deficiency. Evidence for these processes has come slowly and direct effects have remained elusive because plasma Mg levels do not always correlate with its deficiency. Despite the major progress in the understanding of cochlear mechanical and auditory nerve function, the neurochemical and pharmacologic role of Mg is not clear. The putative mechanism suggests that Mg deficiency may contribute to a metabolic cellular cascade of events. Mg deficiency leads to an increased permeability of the calcium channel in the hair cells with a consequent over influx of calcium, an increased release of glutamate via exocytosis, and over stimulation of NMDA receptors on the auditory nerve. This paper provides a current overview of relevant Mg metabolism and deficiency and its influence on hearing.
Keywords: magnesium deficiency; hearing; L-type calcium channel; NMDA; nitric oxide; cochlea; noise; gentamicin; salicylate; outer hair cells; distortion product otoacoustic emissions; transient evoked otoacoustic emissions; cisplatin chemotherapy